2017
DOI: 10.1074/jbc.m116.744755
|View full text |Cite
|
Sign up to set email alerts
|

Critical Contribution of Nuclear Factor Erythroid 2-related Factor 2 (NRF2) to Electrophile-induced Interleukin-11 Production

Abstract: Edited by Joel GottesfeldNuclear factor erythroid 2-related factor 2 (NRF2) is a transcription factor that plays a crucial role in protection of cells from electrophile-induced toxicity through up-regulating phase II detoxifying enzymes and phase III transporters. We previously reported that oxidative stress induces up-regulation of interleukin-11 (IL-11), a member of the IL-6 family that ameliorates acetaminophen-induced liver toxicity. However, a role for IL-11 in protection of cells from electrophile-induce… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 21 publications
(16 citation statements)
references
References 26 publications
(19 reference statements)
0
14
0
Order By: Relevance
“…Since IL-11 + CAFs might promote tumor development, it is crucial to investigate the mechanisms by which inflammation or tumor cells induce IL-11 expression. We previously reported that oxidative stress induces Il11 mRNA expression in an ERK/Fra-1-dependent manner 22, 23 . Thus, we tested whether DSS treatment induced oxidative stress in the colon.…”
Section: Resultsmentioning
confidence: 98%
See 1 more Smart Citation
“…Since IL-11 + CAFs might promote tumor development, it is crucial to investigate the mechanisms by which inflammation or tumor cells induce IL-11 expression. We previously reported that oxidative stress induces Il11 mRNA expression in an ERK/Fra-1-dependent manner 22, 23 . Thus, we tested whether DSS treatment induced oxidative stress in the colon.…”
Section: Resultsmentioning
confidence: 98%
“…IL-11 production is regulated by several cytokines, including TGFβ, IL-1β, IL-17A, and IL-22 18, 19, 20, 21 . We previously demonstrated that IL-11 production is induced by reactive oxygen species (ROS) and the electrophile 1,2-naphthoquinone, which, in turn, promotes liver and intestine tissue repair 22, 23 . While IL-11 is reportedly produced in various cell types (including stromal, hematopoietic, and epithelial cells) in response to different stimuli 16, 17, 24, 25 , the cellular sources of IL-11 in vivo are not fully understood.…”
Section: Introductionmentioning
confidence: 99%
“…Nrf2, also known as nuclear factor (erythroid-derived 2)-like 2, is the principal modulator of encoding genes that protect cells against electrophilic stress. Thus, Nrf2 is comparatively less active in cells without stress, and coordinated with the basal flow of endogenic electrophile [ 160 ]. Activated Nrf2 in an oxidative environment not only illustrates the increasing synthesis of nucleophiles, including GSH and thioredoxin but, also, the enzyme-relevant catalysis for redox transitions [ 161 ].…”
Section: Network Pharmacology-associated Studymentioning
confidence: 99%
“…Moreover, these results suggest that BM‐derived myeloid cells including AMs might promote the regeneration of AEC2s through producing these growth factors or enhancing the production of these factors by lung parenchymal cells. We previously reported that IL‐11 is produced by dying cells and IL‐11 attenuates tissue injury including the liver and intestine through promoting cell proliferation (Nishinaet al, ). Hence, it would be intrigued to test whether transfer of BM cells from Il11 ‐deficient mice into LysM‐DTR mice fails to increase the expression of Il11 , resulting in the impairment of the regeneration of AEC2s in the lung after DT injection.…”
Section: Discussionmentioning
confidence: 99%